2006
DOI: 10.1103/physreve.74.021111
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuation symmetries for work and heat

Abstract: We consider a particle dragged through a medium at constant temperature as described by a Langevin equation with a time-dependent potential. The time dependence is specified by an external protocol. We give conditions on potential and protocol under which the fluctuations of the dissipative work satisfy an exact symmetry for all times. We also present counterexamples to that fluctuation theorem when our conditions are not satisfied. Finally, we consider the dissipated heat, which differs from the work by a tem… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
62
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(71 citation statements)
references
References 26 publications
7
62
2
Order By: Relevance
“…One can check that this identity is verified by all linear diffusion systems studied so far, both theoretically [2,7,8,[14][15][16][17] and experimentally [18,26], although it was unnoticed [27].An example is given in the Supplemental Material [24].…”
Section: Integral Fluctuation Theoremmentioning
confidence: 99%
See 3 more Smart Citations
“…One can check that this identity is verified by all linear diffusion systems studied so far, both theoretically [2,7,8,[14][15][16][17] and experimentally [18,26], although it was unnoticed [27].An example is given in the Supplemental Material [24].…”
Section: Integral Fluctuation Theoremmentioning
confidence: 99%
“…At first sight, µ A (λ) should be the same function for the whole class [A] Qi of observables that differ from Q i by only temporal boundary terms. However, [2] and subsequent work [6][7][8][9][10][11][12][13][14][15][16][17] showed that this is not always true. To see this, it is convenient to rewrite the characteristic function for A ∈ [A] Qi under the alternative form…”
Section: Application To the Prediction Of Rare Eventsmentioning
confidence: 99%
See 2 more Smart Citations
“…A well documented example is that of Brownian particle in contact with one or several heat reservoirs [5][6][7][8][9]. The large deviation function probes exponentially unlikely events for the heat evacuated to the reservoirs.…”
Section: Introductionmentioning
confidence: 99%